2013
DOI: 10.1002/14651858.cd003852.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba for tinnitus

Abstract: The limited evidence does not demonstrate that Ginkgo biloba is effective for tinnitus when this is the primary complaint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 58 publications
0
59
0
1
Order By: Relevance
“…While studies in humans with different Ginkgo biloba extracts so far failed to show any reliable effect on tinnitus perception when given after its development [34, 35], we here tested the effectiveness of a prophylactic treatment with EGb 761 in the context of NIHL and tinnitus development in this animal model. We describe the effects of the EGb 761 extract on the behavioral level (acoustic startle response (ASR) audiometry), the auditory brainstem level (electrophysiological recordings of auditory brainstem responses (ABR)), and the central level (electrophysiological recording of local field potentials (LFP) and single and multiunit responses in auditory cortex (AC)).…”
Section: Introductionmentioning
confidence: 99%
“…While studies in humans with different Ginkgo biloba extracts so far failed to show any reliable effect on tinnitus perception when given after its development [34, 35], we here tested the effectiveness of a prophylactic treatment with EGb 761 in the context of NIHL and tinnitus development in this animal model. We describe the effects of the EGb 761 extract on the behavioral level (acoustic startle response (ASR) audiometry), the auditory brainstem level (electrophysiological recordings of auditory brainstem responses (ABR)), and the central level (electrophysiological recording of local field potentials (LFP) and single and multiunit responses in auditory cortex (AC)).…”
Section: Introductionmentioning
confidence: 99%
“…None found a significant difference (e.g. improvement in tinnitus, 13.6% vs. 12.4%; loudness changed from 42.3dB to 39.0dB vs. 44.1dB to 45.1dB; mean difference in THI between groups –2.5, 95% CI –10.5 to +5.1) 30. The most commonly reported unwanted effect of ginkgo biloba was mild gastrointestinal disturbance (e.g.…”
Section: Drug Treatmentmentioning
confidence: 90%
“…It is thought that ginkgo biloba may promote increased blood flow and alter neurone metabolism 30. There is at least one product with a Traditional Herbal Registration (http://www.mhra.gov.uk/home/groups/par/documents/websiteresources/con051911.pdf).…”
Section: Drug Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A crossover design was used with Ginkgo biloba , since G biloba has been widely promoted as an effective tinnitus treatment. However, multiple, large, well controlled, double-blind, placebo-controlled clinical studies have found that G biloba is no more effective than placebo in alleviating tinnitus 4 11 12…”
Section: Introductionmentioning
confidence: 99%